Роль грызунов фауны Украины в циркуляции гельминтов - Шарпило, Л.Д. (Вестник зоологии, 1976)
Among helminths registered in rodents of the Ukrainian fauna 10 species are presented by larval forms for which rodents are intermediate or reservoir hosts. They play a leading part in infestation of a series of hunting and domestic animals with cestodes (T. mustelae, H. taeniaeformis, T. polyacantha, M. lineatus) and with trematode A. alata. Besides, rodents contribute to preservation and distribution of adult forms of helminths which are of loimological significance: Dicrocoelium lanceatum, Fasciola hepatica, Echinostoma revolutum, Euparyphium melis, Metagonimus yokogawai, Notocotylus attenuatus, Plagiorchis elegans, Psilotrema simillimum, Passerilepis crenata, Rodentolepis straminea, Hepaticola hepatica and others.